Pemahaman Moderasi Beragama bagi Guru Pendidikan Agama Islam di Sekolah - Rohana, Syarifah; Suharman, Suharman (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2023)
Islam is intermediate or balanced in the sense that it is not radical, not extreme and not inclusive (tawasuth). This tawasuth trait must be possessed by everyone, one of which is PAI teachers, because this tawasuth trait is part of religious moderation, a PAI teacher must understand that Indonesia has a very plural diversity. In the midst of this development, a PAI teacher must really understand about moderation, thus teachers can teach their students so that students become ambassadors in peace, love and compassion for others and have a high and good tolerance nature and can be implemented in everyday life. One of the PAI subject matter is that the material on Tasamuh is relevant to the purpose of religious moderation. This article is written using the method of writing literature, by searching, analyzing and analyzing the theories and opinions of figures relevant to the title being discussed, through books, journals and other media